The Design of Nonlinear Chirp Based on the DSP Builder Technique - Zhang Dong; Yang Shou-liang; Zhang Yang (MATEC Web of Conferences, 2017)
This paper, by analyzing the function Chirp, studies the software design and realization of the function. It offers a design plan based on the nonlinear Chirp signal of DSP Builder technique and designs the signal generator of the nonlinear Chirp based on the design flow of Matlab/Simulink/DSP Builder/Quartusll. It also conducts simulation verification using the development software Matlab/Simulink and Quartusll, proving that the design can well realize the signal source Chirp. The experiment proves that the DSP Builder technique can modify the starting frequency, bandwidth and the frequency resolution of linear frequency modulation signals by changing the programming parameters. The method is proved to be simple in designing, convenient in modification, low in cost and it doesn’t involve any programming; therefore, it is easy to realize.